Interlayer Excitons in Transition‐Metal Dichalcogenide Heterobilayers. Issue 12 (25th November 2019) - Nagler, Philipp; Mooshammer, Fabian; Kunstmann, Jens; Ballottin, Mariana V.; Mitioglu, Anatolie; Chernikov, Alexey; Chaves, Andrey; Stein, Frederick; Paradiso, Nicola; Meier, Sebastian; Plechinger, Gerd; Strunk, Christoph; et al.
Abstract : In heterobilayers consisting of different transition‐metal dichalcogenide (TMDC) monolayers, optically excited electron–hole pairs can be spatially separated into the adjacent layers due to a type‐II band alignment. However, they remain Coulomb correlated and form interlayer excitons (ILEs), which recombine radiatively. While these ILEs are observed in several TMDC material combinations, their characters and properties depend on the specific system. Herein, some of these peculiarities are demonstrated by comparing studies performed on two different heterobilayer combinations: MoS2 –WSe2 and MoSe2 –WSe2 . Abstract : In heterobilayers consisting of two different transition‐metal dichalcogenide (TMDC) monolayers, optically generated electron–hole pairs are spatially separated and form interlayer excitons (ILEs), which are observable in photoluminescence. Depending on the specific TMDC combinations, ILEs can be direct or indirect in reciprocal space and show unique properties, such as dipolar exciton–exciton interaction and giant magnetic field–induced energetic splitting.